Current Treatments and New, Tentative Therapies for Parkinson's Disease - Teresa Pardo-Moreno; Victoria García-Morales; Sami Suleiman-Martos; Antonio Rivas-Domínguez; Himan Mohamed-Mohamed; Juan José Ramos-Rodríguez; Lucía Melguizo-Rodríguez; Anabel González-Acedo (MDPI AG, 2023)
Parkinson's disease (PD) is a neurodegenerative pathology, the origin of which is associated with the death of neuronal cells involved in the production of dopamine. The prevalence of PD has increased exponentially. The aim of this review was to describe the novel treatments for PD that are currently under investigation and study and the possible therapeutic targets. The pathophysiology of this disease is based on the formation of alpha-synuclein folds that generate Lewy bodies, which are cytotoxic and reduce dopamine levels. Most pharmacological treatments for PD target alpha-synuclein to reduce the symptoms. These include treatments aimed at reducing the accumulation of alpha-synuclein (epigallocatechin), reducing its clearance via immunotherapy, inhibiting LRRK2, and upregulating cerebrosidase (ambroxol). Parkinson's disease continues to be a pathology of unknown origin that generates a significant social cost for the patients who suffer from it. Although there is still no definitive cure for this disease at present, there are numerous treatments available aimed at reducing the symptomatology of PD in addition to other therapeutic alternatives that are still under investigation. However, the therapeutic approach to this pathology should include a combination of pharmacological and non-pharmacological strategies to maximise outcomes and improve symptomatological control in these patients. It is therefore necessary to delve deeper into the pathophysiology of the disease in order to improve these treatments and therefore the quality of life of the patients.